2011
DOI: 10.1097/aci.0b013e3283481ab6
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of anaphylaxis

Abstract: Recent advances will enhance understanding of the pathophysiology of anaphylaxis and might have future implications for diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 63 publications
0
96
0
8
Order By: Relevance
“…Examples of sudden death syndrome from the medical literature support our hypothesis, including thrombohemorrhagic phenomena (THP), such as anaphylaxis [229,230,[237][238][239], disseminated intravascular coagulation (DIC) [240,241], HELLP syndrome [242], acute liver necrosis [243], Waterhouse-Friderichsen's syndrome, hemolytic uremic anemia, idiopathic pulmonary hemorrhage [244], acute pancreatitis [245], acute pituitary necrosis [246], pseudomembranous colitis, thrombotic thrombocytopenic purpura (TTP), Sanarelli-Shwartzman phenomenon (SSP), Henoch-Schonlein purpura (HSP), eclampsia [238], serum sickness, hemolytic anemia, preeclampsia, and stillbirths [247].…”
Section: Zeta Potential and Cardiovascular Diseasementioning
confidence: 92%
See 2 more Smart Citations
“…Examples of sudden death syndrome from the medical literature support our hypothesis, including thrombohemorrhagic phenomena (THP), such as anaphylaxis [229,230,[237][238][239], disseminated intravascular coagulation (DIC) [240,241], HELLP syndrome [242], acute liver necrosis [243], Waterhouse-Friderichsen's syndrome, hemolytic uremic anemia, idiopathic pulmonary hemorrhage [244], acute pancreatitis [245], acute pituitary necrosis [246], pseudomembranous colitis, thrombotic thrombocytopenic purpura (TTP), Sanarelli-Shwartzman phenomenon (SSP), Henoch-Schonlein purpura (HSP), eclampsia [238], serum sickness, hemolytic anemia, preeclampsia, and stillbirths [247].…”
Section: Zeta Potential and Cardiovascular Diseasementioning
confidence: 92%
“…For this reaction, Richet used a Latin term ana-phylaxis or anti-protection, because the outcome was the opposite from the protection that the vaccine was supposed to provide. In further experiments with numerous other species, including cats, rabbits and horses, Richet showed that anaphylaxis is a universal immune system response [237][238][239]289]. In 1907, Richet demonstrated what is known as passive anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Most recognized is the powerful mast cell activation caused by allergen cross-linking of immunoglobulin E-loaded high-affinity immunoglobulin E receptors (FceRIs), which leads to the release of an array of different mediators. 2 In allergic asthmatics, mast cell mediators such as histamine and prostaglandin D 2 are secreted rapidly after allergen provocation.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 The trigger is either (1) immunologic (IgE or IgG dependent) or (2) non-immunologic (direct stimulation of mast cells by certain drugs, cold air, exercise, etc.). [43][44][45][46] The immunologic pathway involves an allergen-induced crosslinking of IgE antibodies (formed during a clinically silent initial exposure) coupled to mast cells and basophils, which induces a transduction cascade activating mast cells. Note that a very small amount of allergen is needed to trigger the cascade.…”
Section: Pathophysiologymentioning
confidence: 99%